Hypothesizing precise cancer treatments based on patient survival using machine learning & deep learning - Sakib, Hasibul; Alok, Aditto Baidya; Huq, Fardin; Ullah, Shamsil Arafin; Ghosh, Riya (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2023.